CONOMICS OF FLUTED PUMPKIN FARMING IN CALABAR SOUTH LGA, CROSS RIVER STATE, NIGERIA - Akwo, Theresa C.; Uwah, Enoh D.; Uche, Mercy O. (FUDMA Journal of Sciences, 2026)
This study is a profitability assessment of fluted pumpkin farming in Cross River State, Nigeria.  Specifically, it determined the associated cost and returns, evaluated enterprise profitability and ascertained the influence of socio-economic factors on profitability of fluted pumpkin farming in the study area. Multistage sampling was engaged in the selection of respondents, primary data were collected using questionnaire and oral interview and analyzed using descriptive statistics, cost and returns/ profitability analyses and the ordinary least square technique of the   multiple regression analysis. The total cost and revenues per hectare were N218,854.00 and N444,657.00 respectively in the study area. The profitability analysis revealed a positive gross margin of N248,049.00, a net income of N225,803.00 and a benefit cost ratio of 2.03 per hectare implying that fluted pumpkin production is a profitable venture in the study area. The regression analysis showed that cost of labour (1.451) positively and significantly influenced profitability of fluted pumpkin farming at 5% significance  level. The identified constraints were access to capital/ credit, lack of storage facilities and high cost of inputs. The study recommends public/ private sector partnership for enhanced input delivery, intensification of extension education and facilitation of better access to credit.
Keywords: Economics, pumpkin, Profit